Nanoparticles of Organosilane-based NaHSO4 Ionic Liquid Immobilized on Silica as Reusable Heterogeneous Catalyst for One-pot Synthesis of 2-oxo-and thioxo-4-phenyl-1,2,3,4-tetrahydropyrimidines - Abri, Abdolreza; Ghasemian khojasteh, Mohsen (Letters in Organic Chemistry, 2017)
Background: In spite of the fact that there are numerous reagents and methods to synthesize the dihydropyrimidinones via Biginelli reaction, but excellent yields, shorter reaction time and easy work-up are important factors which are not usually found together in a chemical reaction. This work aims to introduce a new reagent with above-mentioned capabilities in mild reaction conditions. Methods: With the benefit of NaHSO4 ionic liquid immobilized on silica as reusable heterogeneous catalyst, prepared via sol-gel method and characterized by SEM and XRD techniques, we could synthesize dihydropyrimidinones derivatives in mild conditions. Results: Data obtained from different identifying techniques, such as SEM and XRD for characterization of the structure of catalyst, and also IR, NMR and Mass spectroscopic techniques for characterization of products obviously confirm the efficacy and integrity of the method. Conclusion: In conclusion, the present procedure provides an efficient reagent for the synthesis of Biginelli compounds. Mild reaction conditions, ease in work-up, high yields, stability and recyclability of the reagent are features of this new procedure.
Keywords: dihydropyrimidinones